Effectiveness and Safety of Indomethacin versus Ibuprofen for the Treatment of Patent Ductus Arteriosus in Preterm Infants - Sivanandan, Sindhu; Bali, Varun; Soraisham, Amuchou Singh; Harabor, Andrei; Kamaluddeen, Majeeda (American Journal of Perinatology, 2013)
Objective To compare the incidence of medical closure of patent ductus arteriosus (PDA) and adverse events (acute renal dysfunction, necrotizing enterocolitis, spontaneous intestinal perforation, and gastrointestinal bleeding) between preterm infants who received indomethacin and ibuprofen for the treatment of PDA.Study Design A retrospective comparative effectiveness evaluation study was conducted on preterm infants (≤32 weeks) who received indomethacin or ibuprofen for treatment of symptomatic PDA.Results Of the 124 eligible infants, 54 received indomethacin and 70 received ibuprofen. The overall incidence of medical PDA closure with indomethacin was 37/54 (68.5%) as compared with 42/70 (60%) in the ibuprofen group (p = 0.32). The proportion of infants with surgical PDA ligation was similar between the two groups (18.5% in both the groups). There was no difference in the incidences of acute renal dysfunction, necrotizing enterocolitis stage ≥ 2, spontaneous intestinal perforation, and gastrointestinal bleeding between indomethacin and ibuprofen groups.Conclusion Ibuprofen is as effective as indomethacin in the treatment of symptomatic PDA in preterm infants. This study also shows that both agents have similar adverse effects and the choice of one agent over the other should be based on local availability and dosing preference.
Keywords: acute renal dysfunction; ibuprofen; indomethacin; patent ductus arteriosus